The Impact of Tax Knowledge on Tax Compliance Case Study in Kota Padang, Indonesia - Fauziati, P.; Minovia, A. F.; Muslim, R. Y.; Nasrah, R. (Journal of Advanced Research in Business and Management Studies, 2020)
c Tax compliance issue is a major problem in revenue generation by government in Kota Padang, Indonesia. This study therefore examines the impact of tax knowlwdge on tax compliance. The survey research design was used in conducting the investigation. The primary source of data was used and three hundred (300) copies of self- administered questionnaire were distributed. The number of questionnaire completed and returned was two hundred and thirty-seven (237), constituting 79% response rate. The simple linier regression models were used to estimate the relationship between tax knowledge and tax compliance. The t-statistics was used to test the significance of the study variables. It was revealed that; tax knowledge has no impact on tax compliance. It is therefore recommended that efforts be made to improve the taxpayers’ knowledge so as to improve tax compliance and consequently improve government revenue generation.